The Inheritance of Historical Trauma: Intergenerational Effects of Early-Life Exposure to Famine on Mental Health - Zihan Zhang; Jun Hyung Kim (Institute of Labor Economics (IZA), 2023)
Can the effects of early childhood trauma persist across generations, impacting the long-run outcomes of their children? To answer this question, we exploit the geographic variation in the intensity of the Great Famine in China and distinguish the effects of exposures during four stages of childhood cognitive development between ages 0 to 15 as defined in the child development theory of Jean Piaget. We find that exposure to famine in childhood, especially in ages 0—2 and 3—7, negatively impacts the adult mental health of the survivors' children. We also find negative effects on parent's mental health and parent-child interaction frequency, consistent with the role of childhood home environments as transmission channels. Our findings show that the determinants of mental health problems can be traced back across a generation and demonstrate the persistent damage of early childhood trauma on the survivors and their children.
Keywords: I14; I18; J13; 330; collective trauma; famine; mental health; intergenerational effects